PRODUCTIVE ZAKAT DISTRIBUTION MODEL IN BAZNAS OF WEST JAVA PROVINCE AND RUMAH ZAKAT OF BANDUNG - Neneng Nurhasanah (AMWALUNA (Jurnal Ekonomi dan Keuangan Syariah), 2021)
This study aimed at comparing the productive zakat distribution model of BAZNAS of West Java Province and Rumah Zakat, their constraints, and efforts conducted in optimizing productive zakat distribution. The study used comparative descriptive method. The results proposed that the productive zakat distribution model of BAZNAS was more varied than at Rumah Zakat’s. BAZNAS conducted traditional consumptive, creative consumptive, traditional productive, and creative productive model using the system of in kind, Al-Qardhul Hasan, and Mudharabah (Revolving Fund System). Meanwhile, there was only one program at Rumah Zakat, namely working capital program to MSMEs handed over directly to Mustahiq, including creative productive zakat distribution. The obstacles faced by BAZNAS was limitations of Mustahiq’s condition so that it took a long time to increase them to Muktafi and then Muzakki. Besides mindset and condition, Rumah Zakat faced capital and market obstacles. Mustahiq’s training and assistance programs were efforts made by these agencies.